THE INFLUENCE OF PROMOTION AND SERVICE QUALITY ON CONSUMER REPURCHASE INTENTION THROUGH CUSTOMER SATISFACTION AT UNDERPRICE SKINCARE JAMIN GINTING, MEDAN CITY - Ridoi Nanda Sinaga; Finta Aramita; Cici Rayani Sitorus; Mey Wiliana Hotmauli Sitorus (RADJA PUBLIKA, 2025)
The purpose of this study was to analyze the effect of promotion and service quality on consumer repurchase interest through customer satisfaction in consumers of Underprice Skincare Jamin Ginting Medan City. The population in this study was 50,492 which was sourced from consumer data for the Underprice Skincare Jamin Ginting store in Medan City, with a sample of 100 respondents determined by the Slovin formula. The data were analyzed using descriptive analysis and SEM (Structural Equation Model) analysis. With the sampling method used is Purposive Sampling. The results show that directly promotion has a positive and significant effect on repurchase interest, service quality has a positive and significant effect on repurchase interest, promotion has no positive and significant effect on customer satisfaction, service quality has a positive and significant effect on customer satisfaction, and customer satisfaction has a negative and significant effect on repurchase interest. Indirectly, promotion has no positive and significant effect on repurchase intention through customer satisfaction, and service quality has a negative and significant effect on repurchase intention through customer satisfaction.